Tenofovir versus placebo to prevent perinatal transmission of hepatitis B - G. Jourdain (2018)
Copyright © 2018 Massachusetts Medical Society. BACKGROUND Pregnant women with an elevated viral load of hepatitis B virus (HBV) have a risk of transmitting infection to their infants, despite the infants' receiving hepatitis B immune globulin. METHODS In this multicenter, double-blind clinical trial performed in Thailand, we randomly assigned hepatitis B e antigen (HBeAg)-positive pregnant women with an alanine aminotransferase level of 60 IU or less per liter to receive tenofovir disoproxil fumarate (TDF) or placebo from 28 weeks of gestation to 2 months post partum. Infants received hepatitis B immune globulin at birth and hepatitis B vaccine at birth and at 1, 2, 4, and 6 months. The primary end point was a hepatitis B surface antigen (HBsAg)-positive status in the infant, confirmed by the HBV DNA level at 6 months of age. We calculated that a sample of 328 women would provide the trial with 90% power to detect a difference of at least 9 percentage points in the transmission rate (expected rate, 3% in the TDF group vs. 12% in the placebo group). RESULTS From January 2013 to August 2015, we enrolled 331 women; 168 women were randomly assigned to the TDF group and 163 to the placebo group. At enrollment, the median gestational age was 28.3 weeks, and the median HBV DNA level was 8.0 log10 IU per milliliter. Among 322 deliveries (97% of the participants), there were 319 singleton births, two twin pairs, and one stillborn infant. The median time from birth to administration of hepatitis B immune globulin was 1.3 hours, and the median time from birth to administration of hepatitis B vaccine was 1.2 hours. In the primary analysis, none of the 147 infants (0%; 95% confidence interval [CI], 0 to 2) in the TDF group were infected, as compared with 3 of 147 (2%; 95% CI, 0 to 6) in the placebo group (P = 0.12). The rate of adverse events did not differ significantly between groups. The incidence of a maternal alanine aminotransferase level of more than 300 IU per liter after discontinuation of the trial regimen was 6% in the TDF group and 3% in the placebo group (P = 0.29). CONCLUSIONS In a setting in which the rate of mother-to-child HBV transmission was low with the administration of hepatitis B immune globulin and hepatitis B vaccine in infants born to HBeAg-positive mothers, the additional maternal use of TDF did not result in a significantly lower rate of transmission. (Funded by the Eunice Kennedy Shriver National Institute of Child Health and Human Development; ClinicalTrials.gov number, NCT01745822.)